United we stand: Double targeting of CD79B and CD20 in diffuse large B‐cell lymphoma. (2nd August 2022) - Tarantelli, Chiara; Bertoni, Francesco
Summary: Polatuzumab vedotin is antibody‐drug conjugate (ADC) targeting CD79B approved for the treatment of patients with relapsed/refractory diffuse large B‐cell lymphoma when given in combination with bendamustine and rituximab. The report by Kawasaki et al. provide hints on what might be happening in lymphoma cells exposed to polatuzumab vedotin and to rituximab and on potential mechanism of resistance to the ADC. Commentary on: Kawasaki et al. The molecular rationale for the combination of polatuzumab vedotin plus rituximab in diffuse large B‐cell lymphoma. Br J Haematol 2022;199:245‐255.